LIVING HADITH IN THE PERSPECTIVE OF THE HAQ NAQSHBANDI SUFI ORDER - Gitosaroso, Muh.; Athoillah, Mohamad Anton; Mukhtar, Naqiyah; Shobirin, Shobirin (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2022)
This study aims to determine the implementation of hadith contents in the tariqa world. The command of the hadith in question is the command of dhikr. Therefore, this article discusses the practice of dhikr orders in hadith, based on the views of the Haq Naqsyabandi Order. This congregation was founded by Maulana Sheikh Tuan Guru Haji Abdussomad Al-Haqqi Habibullah in Lombok, West Nusa Tenggara, in 1986. Its followers have various backgrounds and have spread throughout the archipelago, even in foreign countries. To examine in more depth about this issue, researchers used qualitative methods and phenomenological descriptive research approaches. The data sources in this study are sourced from two things: primary sources (Murshid, Badal Murshid, Foundation Management, College Management, and active congregations) and secondary sources (relevant previous literature studies). The data collection technique in this study is the PAR (Participation Action Research) technique. At the same time, the data analysis technique used the takhrij al-ḥadīth analysis technique followed by sharh al-hadith. This article finds that many scholars recognize the command to dhikr to make Muslims generally remember Allah. However, the scholars still have their respective views on the practice of the command of dhikr from the perspective of hadith, giving rise to many kinds of implementation. Likewise, with the Haq Naqsyabandi Order, the dhikr’s obligation starts from the congregation taking allegiance (tawajjuh) with stages determined and decided by the murshid of the tariqa.[Penelitian ini bertujuan untuk mengetahui tentang bagaimana implementasi makna hadits dalam dunia tarekat. Perintah hadits yang dimaksud adalah perintah dzikir. Oleh karena itu, artikel ini membahas tentang pengamalan perintah dzikir dalam hadits, berdasarkan pandangan Tarekat Haq Naqsyabandi. Tarekat ini adalah sebuah tarekat yang didirikan oleh Maulana Syeikh Tuan Guru Haji Abdussomad Al-Haqqi Habibullah di Lombok, Nusa Tenggara Barat, pada tahun 1986. Para pengikutnya terdiri dari berbagai kalangan, dan telah menyebar ke seluruh nusantara, bahkan di manca negara. Untuk mengkaji secara lebih mendalam mengenai persoalan ini, peneliti menggunakan metode kualitatif dan pendekatan penelitian deskriptif fenomenologis. Sumber data dalam kajian ini bersumber pada dua hal yaitu sumber primer (Mursyid, Badal Mursyid, Pengurus Yayasan, Pengurus Perguruan, dan jamaah aktif) dan sumber sekunder (kajian kepustakaan terdahulu yang terkait). Teknik pengumpulan data dalam kajian ini melalui teknik PAR (Partisipation Action Riseach). Sedangkan teknik analisis data menggunakan teknik analisis takhrīj al-ḥadīth yang dilanjutkan dengan sharḥ al-ḥadīth. Artikel ini menemukan bahwa perintah untuk berdzikir diakui oleh banyak ulama sebagai upaya agar umat Islam secara umum dapat mengingat Allah. Namun, para ulama masih memiliki pandangan masing-masing dalam pengamalan perintah dzikir perspektif hadis sehingga menimbulkan banyak macam pelaksanaannya. Demikian juga dengan Tarekat Haq Naqsyabandi, bahwa kewajiban dzikir dimulai dari sejak jamaah berbai’at (ditawajjuh) dengan tahapan yang telah ditentukan dan diputuskan oleh mursyid tarekat.]